Memaknai Doa Bersama dalam Komunitas sebagai Dasar Pelayanan Pastoral oleh Pengasuh bagi Kaum Disabilitas - Fabianus Selatang; Melfiani Merlin; Witria Wanda; Theresia Mando Tato (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
Surviving and gathering healthily every day, living in communion, eating together, and praising God (Acts 2:41-47) is the way of life of the Early Church. What we want to highlight in this article is a common prayer in the community and how it animates caregivers in all parenting patterns to children/people with special needs. Prayer and community life are typical of Catholics, especially caregivers of the community of ALMA. The aim of the study is to explore the influence of shared prayer in caregiver communities on pastoral care for children/people with special needs. The method used is quantitative inferensial. Quantitative approach used as a step to prove the relationship between variables. Free variables are the common prayers in society, while bound variables are the caregiver services. The population is all caregivers / nurses of children with special needs in Komplek Dieng No. 40, Malang (30 children). Sampling technique used is non probability sampling technique, meaning the entire population was sampled for the study. SPSS version 16 software is used by authors to process data and see the influence between two variables. The level is significant at 5%. The results obtained: 1) The r-table value of 30 samples for free and bound variables is 0.361; 2) free variable reliability test results 0.797>0.6 Cronbach alpa value; while the variable is bound to 0.672; 3) The r-calculated value is v-free and v-bound 0.138931> r-table 0.361. So, H0 was rejected and H1 accepted. As such, there is a positive and significant relationship between shared prayer in the community and caregiver services; 4) Based on a simple linear regression analysis, the constant value of the non-standard coefficient is 32.188, while the regression coefficient value is 0.073. In conclusion, prayer together in the community has a positive effect on caregiver services in the community.